EFFECT OF TRIMETAZIDINE ON MYOCARDIAL KARYOMETRY DURING THE DOXORUBICIN-CYCLOPHOSPHAMIDE MODE OF CHEMOTHERAPY PRESCRIPTION - Авагимян, Ашот Арманович (Medicine in Kuzbass, 2022)
The subject of study. AC-mode of chemotherapy-induced cardiotoxicity, and rationality of trimetazidine prescription. Purpose of the study – research the nuclear apparatus state of rats cardiomyocytes on chronic in vivo model of cancer therapy-driven cardiotoxicity, with a simultaneous assessment and justification for trimetazidine prescription. Research methods. A fundamental, experimental, randomized, and controlled study was carried out. The object of the study was 120 male inbred Wistar rats. Chemotherapy was administered intraperitoneally. The introduction of trimetazidine - intragastrically. An Olympus IX51 microscope was used to assess the changes. Main results. In 2th group on the background of the AC chemotherapy regimen, the value of the nuclear index was higher by 23.1 % and 24.2 % (p < 0.05) than in 1th and 4th groups. In 2th group on the background of AC chemotherapy, the value of the cross-sectional area of cardiomyocytes is higher by 33.3 % and 36.2 % (p < 0.05) than in 1th and 4th groups. In 3th group, against the background of trimetazidine, there is a statistically significant and clinically significant stabilization of the myocardial structure. Application area. Pathological anatomy, cardiology. Conclusions. Trimetazidine is a pathogenetically effective drug that prevent the cardiomyocytes from AC-mode of chemotherapy relared damaged.